Pengaruh Implementasi Perangkat Pembelajaran Biologi Berbasis Potensi Lokal Terhadap Kemampuan Kognitif Peserta Didik - uswatun Hasanah; Mahrus .; Gito Hadiprayitno (Educatio, 2018)
A research has been conducted to determine the effect of the implementation of biological learning tools based the local potential on the cognitive abilities of students in SMAN 1 Lembar. This research is a quasi-experimental research with nonequivalent control group design. The samples of this research were determined by Purposive sampling technique. The two classes were chosen as the sample.The were class X MIPA 2 as the experimental class and class X MIPA 1 as the control class. Hypothesis test using t polled variance test with 5% significant level for pre-test and post-test data then continued with N-Gain improvement test. The results showed the average increasing of learning acievement for student in experimental class was 0,8 (high category) and average increasing in learning outcomes in the control class was 0.6 (medium category). It can be concluded that the implementation of biological learning tools based on the local potential affects the students' cognitive abilities in SMAN 1 Lembar.